2022
DOI: 10.1111/jonm.13887
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' assessment of subsyndromal delirium and barriers to assessment: A cross‐sectional survey in the intensive care unit

Abstract: Aims The aims of the study are to investigate the current status of nurses' assessment of subsyndromal delirium (SSD) in the intensive care unit (ICU) and explore possible barriers to assessment. Background SSD is a dynamic, recognizable disorder commonly seen in the ICU that can lead to poor patient outcomes. Timely recognition and management can prevent its progression. Methods A cross‐sectional survey design was used to collect data from ICU registered nurses in southwest China. The online survey containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Cross-sectional studies found that nurses lack the knowledge and skill to assess delirium. The difficulty of assessing delirium in intubated patients, nurses’ lack of confidence in their ability to use delirium assessment, poor organization and management, and the complexity of patients’ conditions were mentioned as potential barriers to the assessment of delirium ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies found that nurses lack the knowledge and skill to assess delirium. The difficulty of assessing delirium in intubated patients, nurses’ lack of confidence in their ability to use delirium assessment, poor organization and management, and the complexity of patients’ conditions were mentioned as potential barriers to the assessment of delirium ( 38 ).…”
Section: Discussionmentioning
confidence: 99%